Pengaruh Employee Engagement Dan Stres Kerja Terhadap Turnover Intention Karyawan Generasi Z Pada Perusahaan Manufaktur di Kota Depok - Juwita, Beliyana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
Manufacturing companies are among those with a high turnover rate, particularly among Generation Z employees in several areas, such as Depok City. This study aims to analyze the influence of Employee Engagement and Job Stress on Turnover Intention among Generation Z employees working in manufacturing companies in Depok City. The study used quantitative methods, collecting data through questionnaires, and selected 30 respondents using a purposive sampling technique. The data were analyzed using SPSS and multiple linear regression analysis. The results showed that industry effects had a negative and significant effect on turnover, while job stress had a positive and significant effect on turnover. The Adjusted R² test of 0.404 indicated that both independent variables contributed to turnover intention, but the remaining influence was attributed to factors outside the study. These findings suggest that manufacturing companies, particularly those seeking to retain Gen Z employees in Depok City, need to consider factors contributing to turnover intention, including employee engagement and job stress.